Adaptive fuzzy finite-time fault-tolerant attitude control of rigid spacecraft. Issue 10 (October 2015) - Huo, Baoyu; Xia, Yuanqing; Lu, Kunfeng; Fu, Mengyin
Abstract This paper presents the finite-time adaptive fuzzy control to regulate thruster faults in rigid spacecraft system. The considered faults are that the thrusters losing power partially or even totally. Fuzzy logic systems are used to approximate the unknown nonlinear function which is produced by the external disturbances, unknown inertia matrix and thrusters faults. Uniting fast nonsingular terminal sliding mode surface (FNTSMS) and the fault-tolerant control (FTC), two novel adaptive fuzzy finite-time FTC schemes are developed. It has been testified that this control method can make sure that the rigid spacecraft has excellent property of fault-tolerant and all the signals are finite-time convergence. Simulation examples on a rigid body spacecraft with three thrusters and six thrusters are done to indicate that the finite-time FTC schemes are available in achieving high attitude tracking with faults and uncertainty of the system.